1967
DOI: 10.1161/01.cir.35.2.229
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Renal Hemodynamics and Characteristics of Dye-Dilution Curves in Patients with Essential Hypertension and Renal Disease

Abstract: SUMMARYTo gain information concerning cardiorenal hemodynamics in essential hypertension, renal vascular disease, and chronic glomerulonephritis, indocyanine green was used to determine renal blood flow (RBF), renal blood volume (RBV), mean transit time (MTT), appearance time (AT), buildup time (BT), and passage time (PT), in 83 kidneys of 47 hypertensive patients and eight volunteers. Cardiac output (CO) was concurrently measured. Dye, injected into the renal artery, while renal venous blood was drawn through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
1

Year Published

1971
1971
2003
2003

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 45 publications
1
10
1
1
Order By: Relevance
“…Furthermore, the observation that borderline hypertensives show a significantly higher renal plasma flow than normoten sives, both in the control period and during the sodium load, is in agreement with the results obtained by Bianchi et al [28] in nor motensive, first-degree relatives of hyperten sives, but it is in contrast with the decrease in renal plasma flow reported in established hy pertension [30]. Several investigators, work ing with different methods, have observed a significant increase in renal plasma flow in patients with borderline hypertension associ ated with either an increased [24][25][26][27][28][29][30][31] or a normal cardiac output [32], During infusion of inulin and PAH, bor derline hypertensives showed significantly higher values of natriuresis and sodium clear ance than normotensives. This observation is consistent with the data of Baldwin et al [7] obtained in established hypertensives by in fusing inulin and PAH in distilled water.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the observation that borderline hypertensives show a significantly higher renal plasma flow than normoten sives, both in the control period and during the sodium load, is in agreement with the results obtained by Bianchi et al [28] in nor motensive, first-degree relatives of hyperten sives, but it is in contrast with the decrease in renal plasma flow reported in established hy pertension [30]. Several investigators, work ing with different methods, have observed a significant increase in renal plasma flow in patients with borderline hypertension associ ated with either an increased [24][25][26][27][28][29][30][31] or a normal cardiac output [32], During infusion of inulin and PAH, bor derline hypertensives showed significantly higher values of natriuresis and sodium clear ance than normotensives. This observation is consistent with the data of Baldwin et al [7] obtained in established hypertensives by in fusing inulin and PAH in distilled water.…”
Section: Discussionsupporting
confidence: 87%
“…In previous studies we attempted to reduce the influence of the recirculating indicator on the surface calculation by drawing an oblique base line between the pre-and postinjection levels (6,12). Other investigators ignored the second wave and simply extrapolated the exponential downslope to 1% of the curve's peak height (23)(24)(25)(26). A better way is probably to subtract the recirculation wave recorded from the contralateral vein, which yields values that are between those from the two other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Inequality in perfusion between kidneys has been observed in only a few studies. Kioschos et al 12 determined selective renal blood flow by means of the dye dilution technique in 5 normotensive controls and 15 essential hypertensives, including 8 subjects who were suspected of having nephrosclerosis. In 6 of the 15 essential hypertensives, differences in flow between kidneys exceeded 25%, whereas asymmetry was not found in the normotensives.…”
Section: Discussionmentioning
confidence: 99%